Narratives of Song-Based Teaching: Adaptive Strategies and Motivation in Indonesian EFL Context - Zulkifli, Iqbal; Irlina, Andi (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
This study aimed to explore the experiences and adaptive strategies of English teachers for using songs as media in their teaching practices. A qualitative study method with a narrative inquiry approach was applied. Two English teachers from different junior high schools in Banjarmasin were selected as participants. Data was collected through in-depth interviews and supported by classroom observations. The findings revealed that teachers adapted their song-based instruction to suit students’ levels, interests, and classroom dynamics, creating a flexible and engaging environment. The teachers’ motivation to continue using songs emerged from their own enjoyment, increased confidence, and positive student responses, including better participation and language proficiency. The use of song as media also proved technically simple and did not require formal training, making it accessible for broader classroom use. This study highlights the importance of adaptive pedagogical choices and recommends the use of song as a responsive and motivating medium to enhance both teaching effectiveness and student engagement in EFL classrooms.